2001
DOI: 10.4049/jimmunol.166.7.4516
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB and STAT5 Play Important Roles in the Regulation of Mouse Toll-Like Receptor 2 Gene Expression

Abstract: Toll-like receptor 2 (TLR2) is involved in the innate immunity by recognizing various bacterial components. We have previously reported that TLR2 gene expression is rapidly induced by LPS or inflammatory cytokines in macrophages, and by TCR engagement or IL-2/IL-15 stimulation in T cells. Here, to investigate the mechanisms governing TLR2 transcription, we cloned the 5′ upstream region of the mouse TLR2 (mTLR2) gene and mapped its transcriptional start site. The 5′ upstream region of the mTLR2 gene contains tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 41 publications
10
107
1
Order By: Relevance
“…(b) The surface expression of TLRs on naïve CD8 1 T cells is inducible upon TCR activation. While the mechanism is currently unknown, since TLR promoter contains NF-kB binding sites and TCR signals trigger NF-kB activity, it is likely that TCR signals drive TLR expression via activating NF-kB translocation [24]. (c) Once surface located, TLR allow CD8 1 T cells to directly recognise microbial products and further enhance TCR-initiated T-cell activation, suggesting that TLR signals may be essential for optimal antigen-specific CD8 1 T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…(b) The surface expression of TLRs on naïve CD8 1 T cells is inducible upon TCR activation. While the mechanism is currently unknown, since TLR promoter contains NF-kB binding sites and TCR signals trigger NF-kB activity, it is likely that TCR signals drive TLR expression via activating NF-kB translocation [24]. (c) Once surface located, TLR allow CD8 1 T cells to directly recognise microbial products and further enhance TCR-initiated T-cell activation, suggesting that TLR signals may be essential for optimal antigen-specific CD8 1 T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…3A and 5B), suggesting a common signalling pathway. Such a pathway may include the central TLR regulator NF-B, which has been shown to play an essential role in the activation of the mouse TLR2 promoter (Musikacharoen et al, 2001;Wang et al, 2001). The mouse TLR4 promoter does not contain NF-B sites but carries several other elements involved in positive (AP-1, Ets, PU.1) and negative (GATA-1 and Oct-1) regulation of TLR4 transcription (Pedchenko et al, 2005;Roger et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…7). The promoter region of mouse TLR2 contains binding sites for several transcription factors (36), and NF-B is not the only factor contributing to maximal promoter activity. It is suggested that a signal transducer and activator of transcription-binding element also has an impact on the promoter activation (36), and TLR2 could be a gene regulated possibly by TBK1 (70) and interferon regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter region of mouse TLR2 contains binding sites for several transcription factors (36), and NF-B is not the only factor contributing to maximal promoter activity. It is suggested that a signal transducer and activator of transcription-binding element also has an impact on the promoter activation (36), and TLR2 could be a gene regulated possibly by TBK1 (70) and interferon regulatory factors. We suggest that different requirements for NF-B, signal transducer and activator of transcriptions, and interferon regulatory factors in activating the promoters for TLR2, TNF, and RANTES underlie differences in regulation of these three genes induced by different TLR ligands (Fig.…”
Section: Discussionmentioning
confidence: 99%